1997
DOI: 10.1136/fn.76.2.f75
|View full text |Cite
|
Sign up to set email alerts
|

Differential effects of preterm birth and small gestational age on cognitive and motor development

Abstract: Aims-To determine the diVerential effects of preterm birth and being small for gestational age on the cognitive and motor ability of the child. Methods-A longitudinal cohort of all infants of gestational age ≤ 32 weeks born to mothers resident in the counties of Cheshire and Merseyside in 1980-1 was studied. The children were assessed at the age of 8 to 9 years using the Wechsler Intelligence Scale for Children, the Neale analysis of reading ability, and the StottMoyes-Henderson test of motor impairment. Adequ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
78
1
7

Year Published

2001
2001
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 148 publications
(90 citation statements)
references
References 13 publications
4
78
1
7
Order By: Relevance
“…Hutton et al 8 , in a 1997 article, mentioned significant relation between low birth weight with reduced cognitive skills and higher difficulty to read. In prematures, motor skills deficit was predominant 9 .…”
Section: Discussionmentioning
confidence: 99%
“…Hutton et al 8 , in a 1997 article, mentioned significant relation between low birth weight with reduced cognitive skills and higher difficulty to read. In prematures, motor skills deficit was predominant 9 .…”
Section: Discussionmentioning
confidence: 99%
“…Estes resultados são piores do que os relatados na literatura, que mostram médias mais baixas de QI nos grupos de crianças prematuras de muito baixo peso, porém dentro da faixa de normalidade 2,[12][13][14][15] . Em nosso grupo, a média dos resultados alcançados variou de 65 pontos até 89 pontos nos diferentes escores propostos pelo teste (total, verbal e executivo).…”
Section: Discussionunclassified
“…Several past studies comparing SGA children to both birthweight-matched and GA-matched groups indicated that GA and birthweight made independent contributions to outcome (4,5). Other research also supports independent effects on early neurodevelopmental outcomes of different types of complications, including chronic lung disease, retinopathy of prematurity and perinatal brain insult (6).…”
mentioning
confidence: 90%
“…Other research also supports independent effects on early neurodevelopmental outcomes of different types of complications, including chronic lung disease, retinopathy of prematurity and perinatal brain insult (6). It is likely that the effects of SGA vary with the level of GA and that the independent effects of these two factors on cognitive outcomes are obscured by the much larger influences of more extreme preterm birth and attendant neonatal complications (5,7,8). Nevertheless, evidence for independent associations of these several factors with developmental outcomes raises the possibility of distinct pathologies linked to different patterns of cognitive impairment.…”
mentioning
confidence: 97%